Structural geology dataset from Aiguilles Rouges massif (Western Alps) with the associated 3D geological model - Mercier, Antoine; Leloup, Philippe Hervé; Courrioux, Gabriel; Caritg, Séverine; Lopez, Simon; Grandjean, Philippe; Passot, Sophie; Kalifi, Amir (PANGAEA, 2024)
The dataset includes outcrop locations, structural measurements of geological features, and samples used in the study: Large thrusting and late faulting shape the Aiguilles Rouges crystalline massif (Western Alps), structural implications. Data are from the Aiguilles Rouges and Mont-Blanc massifs, two of the External Crystalline Massifs of the Western Alps. The data are given in comma-separated values (CSV). The locations were georeferenced by using hand-GPS devices. Measurements of planar and linear geological features were measured using high-precision professional compasses (Freiberger and Topochaix). The dataset is fully interoperable, with operating standards and lexicons from the international consortium (OGC) and the Darwin Core. This dataset has been used partly for building two 3D geological models based on potential field interpolation (GeoModeller). The data may be helpful for any other structural geologist or engineer who works on the geology of the External Alps and more precisely on the Aiguilles Rouges and Mont-Blanc massif. The dataset includes a 3D photogrammetric model of the highest peak of the Aiguillles Rouges, used for describing the geological features atop the massif. Because the peak is in a high-mountain area, access is quite challenging. Therefore, we acquired high-resolution drone images, to build a 3D photogrammetric digital elevation model (DEM) with Agistoft Metashape 1.7.3 software. The DEM is based on 260 shots with a spatial resolution of about 6 cm.
Keywords: Alps; geological models; Microtectonics; orogenic belts; tectonics